Development of the Reading Ability Entitled “Spelling of Words Ending do not Follow the Rules” by Using Brain Base Learning for Prathomsuksa 2 via the Executive Functions - Jumas, Jitaporn; Kornpuang, Anucha (Ratchaphruek Journal, 2020)
The purpose of the research were to: 1) Compare the reading ability entitled “Spelling of Words Ending do not Follow the Rules” for Prathomsuksa 2 students before and after learning management by the Brain Base Learning with executive functions; and 2) Compare the word reading ability that are spelled inconsistent with the spelling sections of Prathomsuksa 2 students after learning with the criteria of 80 percent. The target group are 9 students in Prathomsuksa 2 in 2nd semester, 2019 academic year of Ban Tha Hae School, Sam Ngam District, Phichit Province. The research plan is a One-group Pretest-Posttest. The research tools were the learning management plan and the ability test. Data were analyzed by percentage, mean ( ), standard deviation (S.D), t-test Dependent and t-test One Sample. The results of the research showed that 1) student had post-test scores higher than pre-test at statistical significant level of .05; 2) Student had higher reading ability on Instruction Entitled Spelling of Words Ending do not Follow the Rules for post-testing than criteria 80 percent at statistical significant level of .05.